2010
DOI: 10.1165/rcmb.2009-0130oc
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters in Airway Parasympathetic Neurons Altered by Neurotrophin-3 and Repeated Allergen Challenge

Abstract: Changes in airway nerves associated with chronic inflammation may underlie the pathogenesis and symptoms of lower airway diseases, such as asthma. The molecules most likely causing such alterations are neurotrophins (NTs) and/or related neurokines. In several species, including humans, lower airway parasympathetic postganglionic neurons that project axons to airway smooth muscle are either cholinergic or nonadrenergic noncholinergic (NANC), the latter synthesizing vasoactive intestinal peptide and nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…However, a number of recent studies have found that the Trk family of receptors (RTK class VII; Fig. 4) that are responsive to the neurotrophin family of growth factors (238) has novel, diverse roles in ASM, including enhancing [Ca 2ϩ ] i and contractility, particularly in the setting of inflammation (120,200,223,236,239,248,268,344). Neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are well recognized in the nervous system for both long-term genomic effects on neuronal growth, differentiation, and survival (181), as well as nongenomic, rapid effects of enhancing [Ca 2ϩ ] i and neurotransmitter release (24,159).…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…However, a number of recent studies have found that the Trk family of receptors (RTK class VII; Fig. 4) that are responsive to the neurotrophin family of growth factors (238) has novel, diverse roles in ASM, including enhancing [Ca 2ϩ ] i and contractility, particularly in the setting of inflammation (120,200,223,236,239,248,268,344). Neurotrophins such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) are well recognized in the nervous system for both long-term genomic effects on neuronal growth, differentiation, and survival (181), as well as nongenomic, rapid effects of enhancing [Ca 2ϩ ] i and neurotransmitter release (24,159).…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…Here, NTs may actually mimic inflammation or other such stimuli. For example, in mice, exogenous NGF enhances airway hyperresponsiveness even in the absence of allergen sensitization and challenge) (Freund-Michel and Frossard, 2008), although this effect does not appear to occur in guinea pigs treated with NGF (Pan et al, 2010). On the other hand, in guinea pigs, BDNF can mimic allergen sensitization by enhancing expression of TRPV1 channels in vagal tracheal cough-causing mechanosensitive neurons of the nodose ganglia, thus enhancing cough reflexes (Lieu et al, 2012).…”
Section: Bdnf In the Lungmentioning
confidence: 99%
“…The parasympathetic nervous system regulates the level and distribution of the signals emanating from the central nervous system and thus plays a pivotal role in the regulation of air flow to the lungs. Because of their peripheral location, parasympathetic nerves may be affected by local inflammation and airway remodeling (18). Although the active and passive (electrophysiological) membrane properties of airway ganglionic neurons have been reported for several mammalian species (13), including humans (8), no studies have focused on mice, a species commonly used in airway asthma and allergy studies (23).…”
mentioning
confidence: 99%